Integrating Digital Technology in Education: The Effectiveness of Mobile Games in Numeracy Learning - I Wayan Wiarta; Maria Goreti Rini Kristiantari; Gusti Ngurah Sastra Agustika (Program Pascasarjana UIN Sumatera Utara, 2025)
The numeracy skills of elementary school students in Indonesia remain low, as reflected in national and international assessments. Conventional teaching methods are ineffective in improving numeracy skills, necessitating a more interactive and engaging approach. This study aims to analyze the effectiveness of mobile game-based learning in facilitating numeracy education. Using a quasi-experimental design, the study involved two groups of third-grade students: an experimental group using mobile games and a control group using PowerPoint. Data were collected through numeracy tests covering number relations, arithmetic operations, and counting. The results showed that the experimental group experienced a significant improvement in numeracy skills compared to the control group, with a p-value of 0.043. These findings suggest that mobile game-based learning is more effective, interactive, and flexible in enhancing students' numeracy skills. The study recommends mobile games as an innovative alternative learning medium in elementary education.